ĐÁNH GIÁ HIỆN TRẠNG MÔI TRƯỜNG ĐẤT KHU VỰC ĐẤT NGẬP NƯỚC XÃ ĐỒNG RUI, HUYỆN TIÊN YÊN, TỈNH QUẢNG NINH - Ngô, Trung Dũng; Nguyễn, Thị Kim Oanh; Nguyễn, Quốc Khánh; Trần, Thị Nhàn; Đặng, Thị Ngọc; Phạm, Viết Thành; Trần, Linh Lan (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF THE STATE OF SOIL QUALITY IN THE WETLAND AREA OF DONG RUI COMMUNE, TIEN YEN DISTRICT, QUANG NINH PROVINCEWetland ecosystems play the most important role but are also vulnerable under economic development activities in estuarine and coastal areas. The quality of the soil environment is an important parameter to assess human impacts on this ecosystem environment. In this study, 28 soil and sediment samples of different types of land use were collected and analyzed with physical indicators (mechanized action, pH, salinity), nutrient indicators (N total, P total, OC, Ca2+, Mg2+) to assess the current state of the soil environment in Dong Rui commune. The results showed a large difference in land indicator groups between 2 groups of land use types distributed inside and outside the levee. For the quality of soil environment in the group of types outside dikes such as river sediments and mangrove soils, the pH value is at a less acidic level, the composition is mainly sand, organic content, high exchange cations. For the group of land use types located inside the dike, the pH value is at the acidity level, the grain level composition is more balanced, the organic content and the ability to exchange cations is low. This difference shows the extent of human impact on these wetlands as well as their natural resilience, particularly in restored forest areas in abandoned shrimp lagoons. This is an important solution in the management and restoration of wetlands in Dong Rui commune.